Reappraisal of VAChT‐Cre: Preference in slow motor neurons innervating type I or IIa muscle fibers. Issue 11 (15th September 2016) - Misawa, Hidemi; Inomata, Daijiro; Kikuchi, Miseri; Maruyama, Sae; Moriwaki, Yasuhiro; Okuda, Takashi; Nukina, Nobuyuki; Yamanaka, Tomoyuki
Summary: VAChT‐Cre.Fast and VAChT‐Cre.Slow mice selectively express Cre recombinase in approximately one half of postnatal somatic motor neurons. The mouse lines have been used in various studies with selective genetic modifications in adult motor neurons. In the present study, we crossed VAChT‐Cre lines with a reporter line, CAG‐Syp/tdTomato, in which synaptophysin‐tdTomato fusion proteins are efficiently sorted to axon terminals, making it possible to label both cell bodies and axon terminals of motor neurons. In the mice, Syp/tdTomato fluorescence preferentially co‐localized with osteopontin, a recently discovered motor neuron marker for slow‐twitch fatigue‐resistant (S) and fast‐twitch fatigue‐resistant (FR) types. The fluorescence did not preferentially co‐localize with matrix metalloproteinase‐9, a marker for fast‐twitch fatigable (FF) motor neurons. In the neuromuscular junctions, Syp/tdTomato fluorescence was detected mainly in motor nerve terminals that innervate type I or IIa muscle fibers. These results suggest that the VAChT‐Cre lines are Cre‐drivers that have selectivity in S and FR motor neurons. In order to avoid confusion, we have changed the mouse line names from VAChT‐Cre.Fast and VAChT‐Cre.Slow to VAChT‐Cre.Early and VAChT‐Cre.Late, respectively. The mouse lines will be useful tools to study slow‐type motor neurons, in relation to physiology and pathology.